An economic analysis of the processing technologies in CDW recycling platforms. (February 2017) - Oliveira Neto, Raul; Gastineau, Pascal; Cazacliu, Bogdan Grigore; Le Guen, Lauredan; Paranhos, Régis Sebben; Petter, Carlos Otávio
Highlights: Economic analysis in the scoping study phase of CDW processing recycling. Economic performances between technological sophistications CDW processing by employing the method of discounted cash flow. Cost estimation of the CDW processing recycling technologies. Abstract: This paper proposes an economic analysis of three different types of processing in CDW (construction and demolition waste) recycling platforms, according to the sophistication of the processing technologies (current advanced, advanced and advanced sorting). The methodology that is adopted is in the economic evaluation concept of projects and is classified with a scoping study phase. In these contexts, three levels of CDW processing capabilities for recycling platforms are analyzed (100, 300 and 600 thousand tons per year). This article considers databases obtained from similar projects that have been published in the specialized literature; the data sources are primarily from the European continent. The paper shows that current advanced process has better economic performance, in terms of IRR, related to the other two processes. The IRR associated with advanced and advanced sorting processes could be raised by, (i) higher price of secondary primary material, and/or (ii) higher capacity of platforms, and/or (iii) higher sharing of secondary primary material in the total production. The first two points depend on the market conditions (prices and total quantity of CDW available) and (potential) fiscal or incentive policies. The last one depends on technological progress.